PERTANGGUNGJAWABAN PERDATA DALAM AKTA PERDAMAIAN (Studi Putusan PN Karawang Nomor 81/PDT.G/2022 PN Kwg) - Muhammad Roikhan Mansyurin; Pamungkas Satya Putra (Universitas Kapuas Sintang, 2023)
This research aims to analyze the Deed of Peace in the Karawang District Court Decision Number 81/PDT.G/2022/PN Kwg based on the legal requirements of the Deed of Peace in the Civil Code. This research method uses a normative juridical method that focuses on studying and examining the law as norms, rules, legal principles, principles, laws, legal doctrines, legal theories. The type of data used in this research is secondary data, through primary legal sources in the form of laws and regulations and secondary legal materials in the form of books and related legal scientific articles. The results showed that the Deed of Settlement of PT Pupuk Kujang as the Plaintiff with PT. Dinamika Kembar Utama refers to the return of the Defendant's debt to the Plaintiff and is made not contrary to laws and regulations, decency, or public interest.Keywords: Deed of Peace, Default, and Court Decision.